Cash Holding, Good Corporate Governance and Firm Value - Nisasmara, Prana Wahyu; Musdholifah, Musdholifah (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2016)
The company’s main goal is to maximize the long term value of the company. The company’s ability to generate value for the company was favorably affected by management’s ability to manage the company. The company expects the financial manager will do the best for the company to increase the value of the company and create wealth for owners and shareholders. This research aims to understand the influence of profitability, capital structure, cash holding, and GCG (Good Corporate Governance) on firm value. The samples of this study were the property sector and real estate companies listed on Indonesia Stock Exchange (IDX) in the period of 2008-2013. The data used from the annual report company. The methods of data analysis were multiple regression models and analyzed using IBM SPSS software. The results of this study are profitability has no influence on firm value, capital structure has positive influence on firm value, cash holding has no influence on firm value and GCG a has a positive influence on firm value.